How Countries Can Fully Implement the New York Convention: A Critical Tool for Enforcement of International Arbitration Decisions - Forneris, Xavier; Mocheva, Nina (In Focus, 2019)
The year 2018 marked the 60th anniversary of the New York Convention on the Recognition and Enforcement of Foreign Arbitral Awards, the most important international convention in the area of international commercial arbitration. The Convention is also said to be the most successful international treaty in the area of private international law. This note primarily targets policy makers and their legal advisors in countries looking at ways to improve their business environment, to become more attractive locations for trade and investment, through better dispute resolution options for international transactions. First, the note explains that international commercial arbitration, as part of countries' legally recognized dispute resolution options, is critical to cross-border contract enforcement. As countries strengthen their international arbitration regimes, they improve their competitiveness in international markets and increase investment and trade by reducing transaction risks and the cost of new infrastructure projects. Countries can improve their international commercial arbitration systems by passing modern legislation consistent with international best practice, ratifying international arbitration conventions, strengthening judicial capacity to enforce arbitral awards, and investing in local arbitration centers.

Rapport sur la situation économique en Mauritanie : améliorer le climat des affaires pour favoriser le développement du secteur privé - Banque mondiale (Groupe de la Banque mondiale, 2019)

COFOLA International 2019: Private Enforcement of Antitrust Law and Unfair Competition with Cross-border Element (Publications of the Masaryk University, theoretical series, editions Scientia, 2019)
Constitutional Questions about the Directive on Antitrust Damages Action ... : The Rule of Binding Effect of National Competition Authorities’ Decisions Arbitrability of the EU Antitrust Law Consumer Decision Making Process as a Centre of the Marketplace Effects Rule
Keywords: Actes de conférence; Competition law; Concorrência desleal; Concurrence (droit); Concurrence déloyale; Droit de la concurrence; E-knihy; Knihy; Litiges internationaux; Mezinárodní spory; Nekalá soutěž; Právo; Právo hospodářské soutěže; Sborníky konferencí; Čítárna

Financing Infrastructure in Africa - Ashiagbor, David; Deiana, Rodrigo; Kappeler, Andreas; Minsat, Arthur; Nguyen-Quoc, Thang; Bank, European Investment (Banking in Africa, 2018)

The Banking Sector in the Central African Economic and Monetary Community (CEMAC): Great Potential in the Face of Enormous Challenges - Benhamdane, Jad; Hidane, Said; Stijns, Jean-Philippe; Bank, European Investment (Banking in Africa, 2018)

Bonne gouvernance et financement des sociétés coopératives en Côte d'Ivoire - Gbede, Jonathan (Friedrich-Ebert-Stiftung Côte d'Ivoire, 2018)
Menée sur une période de deux semaines, dans les localités de Grand-Lahou, Irobo, Dabou, Jacqueville, Songon, Sikensi, Elibou, Tiassalé, Agboville, Akoupé, Adzopé, Yakassé Att obrou, Aff éry, Bonoua, Bassam, Abidjan, Aboisso, Anyama, Bouaké, Yamoussoukro, Djébonoua, Mankono, Korhogo, Boundiali, Vavoua et Odienné, la présente étude vise à amener les sociétés coopératives à s’approprier les principes de bonne gouvernance dans leur quête de fi nancements.

L'intervention du juge dans la vie de la société en droit français et en droit OHADA - Mugisho Kazingufu, Jean-Jacques (Université de Goma, 2017)
Keywords: Corporate law; Droit des sociétés; Intérêt social; Règlement de conflits

Les enjeux de la déjudiciarisation - Cimamonti, Sylvie; Perrier, Jean-Baptiste (Mission de recherche Droit et Justice, 2017)

First Brno Arbitration Conference 2017: Current Issues of International Commercial Arbitration (Publications of the Masaryk University, theoretical series, editions Scientia, 2017)
Content research papers : - The Application of CISG in International Arbitration; - CISG and Arbitration in the Hungarian Legal Practice; - Time Limits in Arbitration Agreements : What Can We Expect, if We Fail to Meet Them? - Interpretation Hardships Regarding the CISG, in Particular Article 7; - Awarding Punitive Damages in Czech Arbitration Proceedings; - Award of Legal Costs in Arbitration with Focus on Regulation in the Slovak Republic; - Advantage or a Disadvantage? The Costs of Arbitration Court Proceedings in Hungary.

Réflexion sur la notion et le régime de la médiation au sein des modes amiables de résolution des différends : à partir des expériences de médiation dans les ressorts des Cours d’appel d’Aquitaine (Agen/Bordeaux/Pau), de Paris et de Lyon - Larribau-Terneyre, Virginie; Lecourt, Arnaud; Brus, Florence; Alvarez Elorza, Alexis; Drouiller, Camille; Sane, Claude MIchel (Mission de recherche Droit et Justice, 2017)

La cyberlégislation et réglementation comme moyen de renforcer le commerce électronique: études de cas et enseignements tirés de l’expérience - Conférence des Nations Unies sur le Commerce et le Développement (CNUCED) (Conseil du commerce et du développement, 2015)
Les transactions électroniques revêtent une importance croissante pour les pouvoirs publics, les entreprises et les consommateurs dans la plupart des pays. Le commerce électronique se développe, créant de nombreuses possibilités, mais se heurte encore à l’obstacle majeur qu’est le manque de sécurité et de confiance. La fraude en ligne et les atteintes à la sécurité des données suscitent des inquiétudes grandissantes et appellent des réponses législatives et réglementaires adéquates, qui permettent de faire croître le commerce intérieur et extérieur. Il n’est cependant pas facile d’adopter un cadre juridique et réglementaire satisfaisant, étant donné la variété et la complexité des législations et réglementations et l’évolution rapide des technologies et des marchés. Les nouveaux modes de paiement et le recours croissant à l’informatique en nuage rendent plus urgent encore le besoin de progrès dans ce domaine. La présente note porte sur les grandes questions juridiques dont il faut tenir compte pour faciliter le commerce électronique et améliorer la sécurité de la communication sur Internet en général. Elle passe brièvement en revue certaines des pratiques les plus indiquées pour surmonter les obstacles bien connus à l’élaboration et à l’application de la cyberlégislation, en prenant appui sur les activités que la CNUCED mène en liaison avec des groupements régionaux de pays en développement. On présente aussi dans cette note les résultats des travaux de la CNUCED sur les lois régissant actuellement ces aspects du commerce électronique, en soulignant les progrès accomplis et les lacunes à combler. On y réfléchit enfin aux moyens d’appliquer et de faire respecter efficacement les lois en vigueur en tenant compte des nouvelles technologies disponibles sur Internet et les appareils mobiles. Les politiques devraient viser à garantir la compatibilité des législations et à renforcer les capacités des principales parties prenantes, notamment les autorités chargées de faire respecter les lois.

Rapport sur l'amélioration du climat des affaires en Afrique Centrale - Commission Économique Pour l'Afrique (Bureau Sous Régional pour l'Afrique Centrale, 2014)

Assessment Report of Arbitration Centres in Côte D’ivoire, Egypt and Mauritius - ORPF (African Development Bank, 2014)

Arbitrating and Mediating Disputes: Benchmarking Arbitration and Mediation Regimes for Commercial Disputes Related to Foreign Direct Investment - Pouget, Sophie (World Bank, 2013)
An effective commercial arbitration regime matters for foreign investors. It gives parties the autonomy to create a dispute resolution system tailored to increasingly complex disputes. Foreign investors view arbitration as a way to mitigate risks by providing legal certainty on enforcement rights, due process, and access to justice. The Arbitrating and Mediating Disputes indicators assess the legal and institutional framework for commercial arbitration, mediation, and conciliation regimes in 100 economies. All surveyed economies recognize arbitration as a tool for resolving commercial disputes and only nine economies have not acceded to the New York Convention on the Recognition and Enforcement of Foreign Arbitral Awards. In the Arbitrating and Mediating Disputes indicators, High Income OECD and Eastern Europe and Central Asia are the regions that reformed their laws on alternative dispute resolution the most between 2011 and 2012. The data also show that, globally, arbitration proceedings take 326 days on average, while recognition and enforcement proceedings of foreign arbitral awards take 557 days on average. The Arbitration and Mediating Disputes indicators are significantly correlated with perception data on the importance of alternative dispute resolution, as well as other measures such as total foreign direct investment inflows and inflows per capita, the Doing Business 2013 Enforcing Contracts data, the World Bank Group's Governance Indicators, the World Economic Forum's Global Competitiveness Indicators, and the Multilateral Investment Guarantee Agency's World Investment and Political Risk data. The paper concludes by identifying several opportunities for improvement, such as greater flexibility for domestic arbitration regimes, faster arbitration proceedings, and better domestic court capabilities.

Trade agreements and bilateral trade in sub-Saharan Africa: Estimating the trade effects of the EU-ACP PTA and RTAs - Turkson, Festus Ebo (CREDIT Research Paper, 2012)
This paper on Trade Agreements within SSA, is an assessment of the ex post bilateral trade effect of the European Union-African Caribbean Pacific Preferential Trade Agreement (EU-ACP PTA) and sub-regional regional trade agreements (RTAs) on bilateral trade involving SSA countries. The main objective is to find out if EU trade preferences and regional trade agreements within SSA had increased trade flows. Estimating a gravity model augmented with measures of trade agreements, the paper made use of bilateral trade flows and key gravity covariates from CEPII database on 73 countries (48 SSA and 25 EU countries) over the period 1960-2006. After controlling for the endogeneity of the trade agreement dummy, accounting for multilateral price resistance and zero-valued trade flows, the findings indicate that the EU-ACP PTA and RTAs within ECOWAS and SADC have a positive and significant impact on bilateral trade involving SSA countries. In some cases the relative impact of the sub-regional RTAs was found to be stronger than the EU-ACP non-reciprocal PTA. The results therefore indicate the need for developing countries especially within SSA to focus on expanding and integrating regional markets in order to significantly improve trade performance.
Keywords: Bilateral Exports; Developing countries; Domestic Trade; Gravity Model; International Trade; Sub-Saharan Africa; Trade Costs

Using observable trade data to measure bilateral trade costs in sub-Saharan Africa - Turkson, Festus Ebo (CREDIT Research Paper, 2012)
Following closely the analytical approach adopted by Head and Mayer (2004) and Novy (2010), this paper derives a micro-founded bilateral trade cost measure for sub-Saharan Africa (SSA) as a function of observable domestic and inter-national trade data. The derived measure of trade cost by Novy (2010), consistent with the Ricardian and heterogeneous firm's models of trade, enables us to track changes in trade costs in SSA over time. This is a significant contribution to the trade cost literature in SSA because measures of many components of trade frictions in SSA have been unreliable. Based on bilateral trade data from BACI and production figures from the Trade, Production and Protection database by Nicita and Olarreaga (2007) for the period 1980-2003, our estimates of the tariff equivalent bilateral trade costs measure indicate that on average trade costs in SSA are relatively higher than other regions, confirming evidence which indicates trading costs in SSA to be the highest within the global trading system. The estimates indicate that SSA countries traded with each other at a lower cost than they did with other regions with the exception of the EU. Within SSA, member countries of economic blocs traded at relatively lower costs than trade with non-member countries. Using each of the main five economic blocs within SSA as a reference, overall average relative bilateral trade costs within bloc was significantly lower than across blocs. This paper therefore argues for increased efforts at regional integration within SSA to derive benefits from lower trade costs.
Keywords: Bilateral Exports; Gravity Model; Sub-Saharan Africa; Trade Costs

La cession de contrôle en droit international privé [Conflict-of-law Rules in Conflict and Competition with Substantive Law Rules: The Case of Corporate Acquisitions] - Kerhuel, Anne-Julie (Georgetown Public Law and Legal Theory Research Paper, 2010)